The Types of Religious Identity of Chechen Students - М. Т. Khaskhanova; M. V. Vereshchagina (Образование и наука)
Introduction. In connection with the growth of religious consciousness of young people in Russia, the study of their religious identity is being updated. Scientists pay special attention to Islamic denominations, as both in Western countries and in the Russian Federation, the number of Muslims is increasing. However, scientific publications cover mainly sociological aspects of the problem, and its psychological component remains insufficiently investigated, which largely determines the social behaviour of a person and affects the process of his or her socialisation. In view of the interest shown by the scientific community in Arab-Muslim culture, appropriate psychological research should be carried out in Muslim-dominated regions. The Chechen Republic is one of such territories in the Russian Federation.The aim is to identify the characteristics and types of religious identity of Chechen students.Methodology and research methods. The study was performed in the framework of socio-psychological approach using the following questionnaires: “Scale of Religious Orientation” by G. Allport, D. Ross; “Structure of Individual Religiosity” by Y. V. Shcherbatykh; questionnaires developed by A. N. Tatarko and N. M. Lebedeva for the study of certainty and valence of ethnic identity and readiness for interethnic interaction; “Types of Ethnic Identity” by G. U. Soldatova and S. V. Ryzhova.Results and scientific novelty. It is revealed that the majority of Chechen students are characterised by consistently internal religious orientation, in which religion is the main value and primary motive of activity. Almost a quarter of respondents demonstrated consistently external religious orientation, characterised by instrumental or external significance. A small group of respondents can be classified as inconsistently religious, whose external religiosity prevails over the internal, and their motivation for behaviour is poorly connected with religion. On the basis of the factor analysis, the types of religious identity of Chechen students are revealed: ethno-cultural, true Muslim, formal, pro-social, non-adaptive, nonreligious, ethnocentric and positive ethnic. The present study evidences that the structure of social identity of students is dominated by ethno-cultural religious identity.Practical significance. The research results extend the knowledge about the content of the concept of “religious identity”, its place in the structure of social identity of the individual, as well as about the relationship of religious orientations with ethnic identity.